If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + -4x) = 6 + -7(2x + 4) (3 * 2 + -4x * 2) = 6 + -7(2x + 4) (6 + -8x) = 6 + -7(2x + 4) Reorder the terms: 6 + -8x = 6 + -7(4 + 2x) 6 + -8x = 6 + (4 * -7 + 2x * -7) 6 + -8x = 6 + (-28 + -14x) Combine like terms: 6 + -28 = -22 6 + -8x = -22 + -14x Solving 6 + -8x = -22 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 6 + -8x + 14x = -22 + -14x + 14x Combine like terms: -8x + 14x = 6x 6 + 6x = -22 + -14x + 14x Combine like terms: -14x + 14x = 0 6 + 6x = -22 + 0 6 + 6x = -22 Add '-6' to each side of the equation. 6 + -6 + 6x = -22 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = -22 + -6 6x = -22 + -6 Combine like terms: -22 + -6 = -28 6x = -28 Divide each side by '6'. x = -4.666666667 Simplifying x = -4.666666667
| 12y+4y=144y | | 4b^2=64 | | 5x+4y=242 | | 20*3= | | 3x+13=25 | | 9-8x= | | -12=2+5n+2v | | (0.4a-0.1)(0.07a+1)=0 | | 16y+2(2y+3)=16 | | 6y-8y-3=10 | | 2b-5-5b-9= | | X-.0275X=80.25 | | 0.2b+5=0.5b+14 | | 5x+xy=y | | (6-4)x49/7 | | X-.0275*X=97.25 | | 5x+12=-2x(-7)+12 | | (x^2)-(20x)+1=0 | | 25/40=60/x | | -3(4-(3b+3))=6-3(3b+8) | | 5x+15=8x-6 | | 8-(6-8x)=4x+13 | | 0.05(8-x)+0.1x=0.64 | | 5x-34=0 | | 8(2x+3)=72 | | P/9=97 | | (p/9)=97 | | x=2/3+9-3 | | 4x^2+9y^2-16x+54y+61=0 | | 10n^2+490n-4000=0 | | 4/3=5/12+3x/7 | | 3(4x+8)=36 |